Caregiver burden among parents of children with type 1 diabetes: A qualitative scoping review - Tara Azimi; Jeff Johnson; Sandra M. Campbell; Stephanie Montesanti (Heliyon, 2024)
Objectives: Type one diabetes (T1D) in children places substantial responsibility on parents as caregivers. This study investigated caregiver burden in parents of children with T1D by exploring the financial, physical, social, spiritual, and emotional or psychological problems they experienced. Methods: We conducted a qualitative scoping review of the databases PsycINFO, PROSPERO, OVID Medline, OVID EMBASE, Cochrane Library (CDSR and Central), EBSCO CINAHL, ProQuest Dissertations and Theses Global, and SCOPUS. Of 119 full text articles assessed for eligibility, 18 peer-reviewed qualitative studies were included. Studies were considered relevant if they focused on diabetes management and parental burden or the experience of caregiving for a child with T1D. Results: Using thematic analysis, six interrelated themes were identified: (a) experiencing chronic sorrow, (b) assuming responsibility for glucose highs and lows, (c) managing T1D and nighttime sleep disturbances, (d) making career sacrifices and choices to optimize T1D care, (e) navigating social experiences postdiagnosis, and (f) discovering new sources of support through online platforms. Conclusions: This synthesis highlights an all-encompassing experience involved in caretaking for a child with T1D. Caregiving duties lead to a constant sense of vigilance, especially due to fear of hypoglycemic incidents. Parents commonly experience challenges with balancing work demands with T1D management, which lead to career and financial sacrifices. Their burden of care is exacerbated by a lack of reliable respite care but helped somewhat by online peer support. Future research is needed on the care burden differences between mothers and fathers and how sociodemographic factors affect how caregiver burden is experienced.